Effects of Organic Acids on Sucrose Conversion in Preserved Cherry Tomato Syrup and Analysis of Methods for Its Deacidification and Depectinization - XIE Songming, ZHANG Siyuan, LI Shihao, SUN Minmin, WANG Zhijun, CAO Jiankang (Shipin Kexue, 2025)
This study explored the effects of malic acid, citric acid, and their combination on sucrose conversion in a simulated preserved cherry tomato syrup under heating conditions. The results showed that the content of reducing sugar generated by sucrose conversion increased with increasing concentration of the two organic acids and their 1:1 (m/m) mixture. When citric acid and malic acid were combined in a ratio of 2:1 (m/m), the reducing sugar content in the sucrose solution reached its maximum level. During the candying of cherry tomato, the contents of total sugar and sucrose in the syrup decreased with increasing number of boiling cycles, while the contents of reducing sugar, fructose, pectin, and total acid increased. Three deacidification methods and four depectinization methods for the syrup were evaluated. The mass of substances required to deacidify the syrup decreased in the order of calcium carbonate > sodium bicarbonate > calcium hydroxide. The removal rates of pectin from the syrup treated with calcium hydroxide and gelatin and diatomaceous earth were 42.4% and 60.2%, respectively. Calcium hydroxide treatment provided more pronounced removal of pectin under heating conditions than at room temperature, and the effect increased first and then decreased with the increase in pH. Centrifugation effectively increased the light transmittance of the syrup and reduced its pectin content by 24.0%–43.2%. The pectin removal rate after filtration by filter paper or filter membrane was between 32.3% and 34.0%. These findings provide theoretical insights into the conversion of sucrose in preserved cherry tomato syrup and offer practical approaches for the deacidification, depectinization and reuse of the syrup.